Rationale and Description of Implementation of Regional Collaborative Service Model for Enhancing Psychosocial Wellbeing of Children and Families—Oulu Collective Impact Study - Takalo, Tuula; Räsänen, Sami; Hakko, Helinä; Juutinen, Aapo; Niemelä, Mika (Frontiers in Psychiatry, 2022)
Background: The psychosocial wellbeing of children and adolescents is an ongoing global concern. Despite positive outcomes of child- and family-focused programs, the fragmentation of services presents challenges. To enhance harmonization and diminish fragmentation of service policies, we implement a preventive collaborative service model for children and families. The rationale for our study is based on analyses of national and local data before implementing the service model in the pilot area. Methods: The need for a preventive service model for children and families was demonstrated using national and local data sources. First, a national school health survey was utilized to screen adolescents’ perceptions of their depressive symptoms and support. Second, time trends in child and adolescent psychiatric and child protection service use were investigated. For these aims, epidemiological data of the study area (city of Oulu) were compared with data from the whole country (Finland). Third, local usage data of the preventive stand-alone LT intervention before the service model implementation were evaluated. After these analyses, LT-SM model implementation in the pilot area is described in detail. Results: The background data showed that 17% of the adolescents in the study area had reported depressive symptoms and almost half of them had not received professional help. Child and adolescent psychiatric outpatient visits had increased during the last decade, but the number of visits remains lower in the study area compared to the country as a whole. The number of adolescent psychiatric inpatient days had increased contrary to a decreasing national trend. The number of urgent child welfare placements was also higher compared to the whole country. The local LT intervention data revealed very low utilization rates. These results indicated a necessity to enhance preventive and collaborative support for children and their families. This article describes the implementation of the LT-SM model. Discussion: We demonstrated excessive use of curative services in social and health care and insufficient usage of the stand-alone preventive intervention. The LT-SM model is now piloted in one regional service area of the city of Oulu. Its effectiveness will be evaluated when enough data has accumulated for statistical analyses.